If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying 5x^{2}+ 11x + 1 = 0 Reorder the terms: 1 + 11x + 5x^{2}= 0 Solving 1 + 11x + 5x^{2}= 0 Solving for variable 'x'. Begin completing the square. Divide all terms by 5 the coefficient of the squared term: Divide each side by '5'. 0.2 + 2.2x + x^{2}= 0 Move the constant term to the right: Add '-0.2' to each side of the equation. 0.2 + 2.2x + -0.2 + x^{2}= 0 + -0.2 Reorder the terms: 0.2 + -0.2 + 2.2x + x^{2}= 0 + -0.2 Combine like terms: 0.2 + -0.2 = 0.0 0.0 + 2.2x + x^{2}= 0 + -0.2 2.2x + x^{2}= 0 + -0.2 Combine like terms: 0 + -0.2 = -0.2 2.2x + x^{2}= -0.2 The x term is 2.2x. Take half its coefficient (1.1). Square it (1.21) and add it to both sides. Add '1.21' to each side of the equation. 2.2x + 1.21 + x^{2}= -0.2 + 1.21 Reorder the terms: 1.21 + 2.2x + x^{2}= -0.2 + 1.21 Combine like terms: -0.2 + 1.21 = 1.01 1.21 + 2.2x + x^{2}= 1.01 Factor a perfect square on the left side: (x + 1.1)(x + 1.1) = 1.01 Calculate the square root of the right side: 1.004987562 Break this problem into two subproblems by setting (x + 1.1) equal to 1.004987562 and -1.004987562.## Subproblem 1

x + 1.1 = 1.004987562 Simplifying x + 1.1 = 1.004987562 Reorder the terms: 1.1 + x = 1.004987562 Solving 1.1 + x = 1.004987562 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1.1' to each side of the equation. 1.1 + -1.1 + x = 1.004987562 + -1.1 Combine like terms: 1.1 + -1.1 = 0.0 0.0 + x = 1.004987562 + -1.1 x = 1.004987562 + -1.1 Combine like terms: 1.004987562 + -1.1 = -0.095012438 x = -0.095012438 Simplifying x = -0.095012438## Subproblem 2

x + 1.1 = -1.004987562 Simplifying x + 1.1 = -1.004987562 Reorder the terms: 1.1 + x = -1.004987562 Solving 1.1 + x = -1.004987562 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1.1' to each side of the equation. 1.1 + -1.1 + x = -1.004987562 + -1.1 Combine like terms: 1.1 + -1.1 = 0.0 0.0 + x = -1.004987562 + -1.1 x = -1.004987562 + -1.1 Combine like terms: -1.004987562 + -1.1 = -2.104987562 x = -2.104987562 Simplifying x = -2.104987562## Solution

The solution to the problem is based on the solutions from the subproblems. x = {-0.095012438, -2.104987562}

| y^2-16y-4= | | y=5x^2-3x+5 | | 7x-28=2x^2-8x-3x+12 | | y=x^2+5x | | y=x^2+2x | | x^7-5x^5+x^2-5=0 | | 15x^2-8x-7=0 | | X^2+6x-27=0 | | 3x^2-6x+12=0 | | (4x^3-6x^2+5)-(8x^2+3x-6)= | | 11x^2-2x+9=0 | | 4x(2x^2-6x-5)= | | 10x^2+5x+8=0 | | 9x^2+9x+8=0 | | 12x^2+5x+10=0 | | 9x^2+21x+12=0 | | -2x^2+4x+12=0 | | 3x^2+10x+8=0 | | -8x^2+8x-2=0 | | X^2-x-2=0 | | 3x^2+x-1=0 | | (8x^4+5x^3-5)-(5x^2-6x+4)= | | 2x^2+10x+12=0 | | (7m^8-5m^3+9m^2+5)+(9m^7+3m^3-4m)= | | X^2-5x-48=0 | | X^2-12x+20=0 | | x^4-4x^3+5x^4-9x^3+2= | | (6x^4y^3+9x^3y^2)+(3x^3y^3-2x^3y^2-7xy)= | | y=x^3+3x^2-9x-8 | | 4x^4+3x^2-1=0 | | kx^2+4x+(5-k)=0 | | 12a^4b^3=0 |

- Equations solver - equations involving one unknown
- Quadratic equations solver
- Percentage Calculator - Step by step
- Derivative calculator - step by step
- Graphs of functions
- Factorization
- Greatest Common Factor
- Least Common Multiple
- System of equations - step by step solver
- Fractions calculator - step by step
- Theory in mathematics
- Roman numerals conversion
- Tip calculator
- Numbers as decimals, fractions, percentages
- More or less than - questions